PERANCANGAN BUKU CERITA ILUSTRASI BERJUDUL “MENGENAL ZAMAN NEOLITIKUM BERSAMA KELUARGA BUDI” UNTUK ANAK USIA 5-8 TAHUN - Martinus Eko Prasetyo Kaparang; Richard Manuela (Jurnal Bahasa Rupa, 2022)
The design of this work was made with the aim of increasing the enthusiasm of children aged 5-8 years to read and providing insight into the history of the Neolithic Age by using a 2D illustration approach so that visuals can look more fun and not boring for students. Because not many students aged 5-8 years are interested enough in learning about history but most of the history books nowadays look boring with too many texts. The need for a media book that is able to make students interested in learning, therefore with this illustration book it is hoped that it can make it easy for children to understand and understand history lessons because this illustration book uses sentences that are easy for children to understand. 5-8 years. The research method was carried out by conducting interviews with informants, distributing questionnaires, and collecting and reading literature. The final result of this design is a 2D illustrated history story book using a family approach so that children can feel close to the storyline and the characters in the illustrated stories in the book. This illustrated book generated a positive response to the students, because the appearance of the history learning book with an illustration style at least did not make them bored quickly to read. Of course, it is hoped that it can provide insight to children about the history of the neolithic era which can increase interest in reading for children aged 5-8 years.